2017
DOI: 10.1093/gji/ggx307
|View full text |Cite
|
Sign up to set email alerts
|

Subduction and vertical coastal motions in the eastern Mediterranean

Abstract: S U M M A R YConvergence in the eastern Mediterranean of oceanic Nubia with Anatolia and the Aegean is complex and poorly understood. Large volumes of sediment obscure the shallow structure of the subduction zone, and since much of the convergence is accommodated aseismically, there are limited earthquake data to constrain its kinematics. We present new source models for recent earthquakes, combining these with field observations, published GPS velocities and reflection-seismic data to investigate faulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 158 publications
(299 reference statements)
9
55
0
Order By: Relevance
“…Extensional faults that trend parallel to the Hellenic arc, such as those discussed in this study, exist offshore and onshore southern Crete (e.g., Sfakia fault and Selia/Assomatos faults, Figure a), Kythira, the Mani Peninsula (Peloponnese), and western Peloponnese (Armijo et al, ; Gaki‐Papanastassiou et al, ; Kassaras et al, ; Kokinou & Kamberis, ; Mascle et al, ; Papanikolaou et al, ; Papoulia et al, ; Papoulia & Makris, ; Tsimi et al, ; Wardell et al, ) and are in many places associated with uplifted marine terraces (e.g., Angelier, ; Athanassas & Fountoulis, ; Gaki‐Papanastassiou et al, ; Kelletat et al, ). The presence of terraces and onshore/offshore extensional faults throughout the rest of the Hellenic Arc leads us to suggest the observed uplift along these coastlines could, in part, also be controlled by upper‐plate faults; there is evidence that terraces along the western Peloponnese are on a length scale associated with upper‐plate extensional faults (Howell et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensional faults that trend parallel to the Hellenic arc, such as those discussed in this study, exist offshore and onshore southern Crete (e.g., Sfakia fault and Selia/Assomatos faults, Figure a), Kythira, the Mani Peninsula (Peloponnese), and western Peloponnese (Armijo et al, ; Gaki‐Papanastassiou et al, ; Kassaras et al, ; Kokinou & Kamberis, ; Mascle et al, ; Papanikolaou et al, ; Papoulia et al, ; Papoulia & Makris, ; Tsimi et al, ; Wardell et al, ) and are in many places associated with uplifted marine terraces (e.g., Angelier, ; Athanassas & Fountoulis, ; Gaki‐Papanastassiou et al, ; Kelletat et al, ). The presence of terraces and onshore/offshore extensional faults throughout the rest of the Hellenic Arc leads us to suggest the observed uplift along these coastlines could, in part, also be controlled by upper‐plate faults; there is evidence that terraces along the western Peloponnese are on a length scale associated with upper‐plate extensional faults (Howell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of uplift on Crete is debated and suggested to result from underplating on the subduction interface, reverse motion on the megathrust, thrusting and oblique slip faulting in the forearc, and active normal faulting (Angelier et al, 1982;Caputo et al, 2010;Gallen et al, 2014;Ganas & Parsons, 2009;Meier et al, 2007;Shaw et al, 2008;Strobl et al, 2014;Taymaz et al, 1990;Tiberti et al, 2014). Geodetic, seismological, and geological evidence suggests compressional, extensional, and strike-slip tectonics onshore and offshore southern Crete as seen by the analysis of fault plane solutions and microseismicity studies Bohnhoff et al, 2005;Caputo et al, 2010;Doutsos & Kokkalas, 2001;Howell et al, 2017;Kokinou et al, 2012;Meier et al, 2007;Papazachos, 1990;Taymaz et al, 1990). These studies show that thrust faulting occurs as a result of forearcnormal compression at depths linked to subduction to the south of Crete; additionally, Shaw et al (2008) suggested that reverse (high-angle) splay faults may cut the upper crust in western Crete; however, their existence was debated by Ganas and Parsons (2009) on the basis of a lack of compatible seismological data.…”
Section: 1029/2018tc005410mentioning
confidence: 99%
See 1 more Smart Citation
“…Seismicity (Kalyoncuoğlu et al, 2011;Howell et al, 2017) and seismic tomography (Biryol et al, 2011;van der Meer et al, 2018) show that the top of the Antalya slab is currently located below the Gulf of Antalya, more than 150 km southwest of Tauride thrusts that mark the Eocene plate boundary. This slab must contain the mantle underpinnings of Taurides, which have now sunk into the mantle.…”
Section: ■ 6 Discussionmentioning
confidence: 99%
“…The Florence Rise (Fig. 9, from Howell et al 2017) and Apscheron Sill across the middle of the Caspian Sea (Fig. 10) are two relatively small structures that have subducted oceanic lithosphere in the Alpine-Himalayan collision zone.…”
Section: Subduction In the Mediterranean Region And The Indo-burma Ramentioning
confidence: 99%